Pattern of Specific Oxidation of Konjac Glucomannan with TEMPO/NaBr/NaClO system. (May 2022) - Wu, Fangxia; Yan, Na; Guo, Yan; Yu, Xiaoxiao; Yi, Lin; Ouyang, Yilan; Wang, Xin; Zhang, Zhenqing
Abstract: The TEMPO/NaBr/NaClO system was used to modify konjac glucomannan and prepare β-1, 4-linked D-mannuronic/glucuronic acid oligosaccharides. The impact of oxidant amount on the degree of oxidation, molecular weight, terminal structure and the ratio of sugar units were systematically investigated. Mannoses were transformed to mannuronic acids quantitatively, while some glucose were transformed to glucuronic acids, some degraded. The unspecific oxidation causes strong degradation of konjac glucomannan sugar chains. Multiple terminal structures were observed in the oxidized KGM products. According to those observations, the oxidation pattern of konjac glucomannan with the TEMPO/NaBr/NaClO system was speculated. It is suggested that the axial hydroxyl group at position 2 in mannose might form a hydrogen bond with the oxygen on the sugar ring. It would against the unspecific oxidation. While, both specific and unspecific oxidations were observed at glucose units with an equatorial hydroxyl group at position 2, and the degradation occurs mostly on glucose during the oxidation. Graphical abstract: Image 1 Highlights: TEMPO/NaBr/NaClO system was used to modify konjac glucomannan. The structure of oxidized konjac glucomannan was fully characterized. Mannose is more stable than glucose in the KGM during oxidation. The oxidation pattern of KGM with the TEMPO/NaBr/NaClO system was speculated.